Penerapan Prinsip Rancangan Tadao Ando Pada Fasilitas Kegiatan Rohani Kristen Di Pulau Bintan - Yuda Dodianju Munthe; Mira Dharma. S; Yohanes Firzal (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2020)
Christian spiritual activities are public activities for Christians / congregants, such as worship, prayer and spiritual performances as well as public activities, whether sports, arts, organization / community, place of formation, training, performances and social activitiesand various activities which are shared (Pasla & et al, 2015). The needs of Christians for spiritual facilities are very basic and important needs. So far the facilities provided by the parent organization of the congregation to the congregation have only been completed by theconstruction of a church building and manse and often forget the considerations of other facilities that can support various other spiritual activities besides worshiping. The Christian Spiritual Activity Facility is also expected to become a place that can accommodate variousspiritual activities with adequate facilities, become a training ground for anyone who has the desire to develop talents to serve God and even is expected to become a new religious tourism site on Bintan Island . Christian Spiritual Activity Facility will be located in Tanjungpinang Timur sub-district. This location was chosen based on data from the Central Statistics Agency in 2018 which states that the largest distribution of Christians is in the District of East Tanjungpinang. In the design of the Spiritual Activity Facility on Bintan Island, the Tadao Ando principle will be used. Tadao Ando introduced a theory of modernism which he called "Zen Minimalism". Zen minimalism is a design concept that is basically acombination of the concept of simplicity of form, naturalness, and the concept of emptiness in human beings themselves. Simplicity and emptiness transformed into a concept where thesimplicity of everything can lead a person to achieve a void of self in order to realize that he is a part of nature (Ando in Kapugu, 2017).keywords: Christian Spiritual Activity Facility, Tadao Ando, Bintan, Tanjungpinang